2004
DOI: 10.1063/1.1798991
|View full text |Cite
|
Sign up to set email alerts
|

Importance of chain–chain interactions on the band gap of trans-polyacetylene as predicted by second-order perturbation theory

Abstract: We employ the Laplace-transformed second-order Moller-Plesset perturbation theory for periodic systems in its atomic orbital basis formulation to determine the geometric structure and band gap of interacting polyacetylene chains. We have studied single, double, and triple chains, and also two-dimensional crystals. We estimate from first principles the equilibrium interchain distance and setting angle, along with binding energy between trans-polyacetylene chains due to dispersion interactions. The dependence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…[25] It was shown that band gaps predicted for conducting polymers using the hybrid B3LYP functional coupled with PBC were in excellent agreement with experimental values. [26] We are aware that DFT, in general, and the B3LYP hybrid density functional, in particular, overestimate twisting energies compared to the ab initio MP2 method. [12a] However, a recent report has shown that the discrepancies between the DFT and MP2 studies observed earlier are mainly caused by the use of a small basis set for the MP2 calculations, and B3LYP results are close to the benchmark at CCSD(T)/cc-pVDZ, while increasing the basis set for MP2 calculations also brings the MP2 results close to the benchmark.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…[25] It was shown that band gaps predicted for conducting polymers using the hybrid B3LYP functional coupled with PBC were in excellent agreement with experimental values. [26] We are aware that DFT, in general, and the B3LYP hybrid density functional, in particular, overestimate twisting energies compared to the ab initio MP2 method. [12a] However, a recent report has shown that the discrepancies between the DFT and MP2 studies observed earlier are mainly caused by the use of a small basis set for the MP2 calculations, and B3LYP results are close to the benchmark at CCSD(T)/cc-pVDZ, while increasing the basis set for MP2 calculations also brings the MP2 results close to the benchmark.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…We distinguish polyacetylene (pA), the infinite chain, from its shortest oligomers (nA). Actually, the difference between single and double bond lengths in several oligomers of increasing size has recently received much attention [108][109][110][111][112] due to the generalized failure of DFT models. The key parameter ruling the performance of the large set of functionals tested was found again the compromise between exact-like and density-based exchange.…”
Section: Oligoenes: Bond-length Alternation and Proton Affinitiesmentioning
confidence: 99%
“…Bond-length alternation (BLA), defined as the difference between the central C-C bond and any of the adjacent double bonds when imposing a C 2h symmetry, is calculated for a set of increasingly longer oligoenes. The cost-effective 6-31G * is consistently used [108,109]. Note that best estimates of BLA have only recently become available [60] for some short oligomers.…”
Section: Oligoenes: Bond-length Alternation and Proton Affinitiesmentioning
confidence: 99%
“…These approximations result in a substantial reduction in calculation time, and thus the DFT method has been successfully applied to study some large and periodic systems, such as single-walled carbon nanotubes, [17] polymers, [18] clay minerals, and zeolites. [19] It is reasonable to expect that DFT should be suitable for the study of nanocomposites of PANI/ layered compounds.…”
Section: Computational Detailsmentioning
confidence: 99%